The effect of local minerals on the productivity of meat chickens - Daurenbekov Khanibek; Zhilkibaev Aset; Asylbekov Bauyrzhan; Fayzullayeva Lazzat; Iskakova Aksaule (E3S Web of Conferences)
Among the mineral feeds, the most popular is the snail shell, because the progenitors of this mineral feed were living organisms. The level of digestion in the bird's body is much higher than in other mineral substances. One of the most fundamental factors of all experiments is the economic efficiency of the experiments done. Therefore, we calculated the effectiveness of feed lime given to broiler chickens with zootechnical indicators and put them in the fifth table. Therefore, the search for mineral feed sources, the determination of their composition parts, the determination of the presence of additives that can harm poultry, and if everything is correct, the use of new sources of mineral feed in production is one of the most relevant and urgent issues today.